2021
DOI: 10.3390/su13084347
|View full text |Cite
|
Sign up to set email alerts
|

Terraced Landscapes Regeneration in the Perspective of the Circular Economy

Abstract: Terraced landscapes were for centuries forms of sustainable and multifunctional land management, results of a long and intimate relationship between peoples and their environment. They demonstrated a rich cultural diversity and agrobiodiversity through sustainable land-use systems. These productive cultural landscapes in many cases were expressions of a pre-industrial circular model of rural development, where no resource was wasted. However, not all terraced landscapes have to be considered sustainable in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Parallelly, using a circular economy (CE) helps develop a participatory governance or management system, mitigating financial risks and pressure. Thus, a CE fosters the socioeconomic contexts including equity, social inclusion and exchanged and/or joint responsibility in a sustainable manner [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallelly, using a circular economy (CE) helps develop a participatory governance or management system, mitigating financial risks and pressure. Thus, a CE fosters the socioeconomic contexts including equity, social inclusion and exchanged and/or joint responsibility in a sustainable manner [4].…”
Section: Introductionmentioning
confidence: 99%
“…These activities can preserve cultural asset(s) by providing multifunctionality on the ecological, social, cultural, and economic ground with less negative impacts on the host communities and slower/controlled modifications in the local economy. This could provide an authentic tourism experience with respect to the heritage community [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Modica et al [16] observed a drastic reduction (−85.4%) in cultivated terraces between 1955 and 2014 in Costa Viola (Calabria, Italy), confirming the negative trend and highlighting the importance of maintaining sustainable agriculture and enhancing terraced systems. In effect, enhancing terraced landscapes using an innovative regeneration approach from a past-to-future perspective is an important challenge to developing sustainable agriculture and reactivating a local circular economy [17]. Indeed, this particular type of rural landscape needs sustainable practices that highlight historical value and mitigate threats [18].…”
Section: Introduction 1terraced Landscapes and Rural Communitiesmentioning
confidence: 99%
“…Terracing can increase arable land and agricultural production [3,4] and contribute to soil and water conservation [5,6] by changing the local topography of slopes and their corresponding water flow process [7] and soil properties [8]. The artificially terraced landscapes that have been developed widely around the world [2,9] can enhance biodiversity and landscape diversity [10,11] and provide aesthetic, cultural, and tourism landscape value [12][13][14]. However, localised movement and erosion are likely to occur on terraced fields due to steep ridges, as manifested by the micro-landforms of terrace damages, including collapse and sinkholes [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…J. Geo-Inf. 2021, 10, x FOR PEER REVIEW 2 of 19 versity and landscape diversity [10,11] and provide aesthetic, cultural, and tourism landscape value [12][13][14]. However, localised movement and erosion are likely to occur on terraced fields due to steep ridges, as manifested by the micro-landforms of terrace damages, including collapse and sinkholes [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%